Productivity and Convergence in a Panel of OECD Industries Do Regulations and Institutions Matter? - Scarpetta, Stefano (OECD Economics Department Working Papers, 2002)
We analyse the impact of innovation activity and product and labour market institutions on multi-factor productivity in a panel of 23 industries in 18 OECD countries using a novel harmonised database. First, we provide evidence of convergence in productivity levels within most industries across OECD countries. Convergence is however stronger in services than in manufacturing and, in the latter sector, it is weaker for high-tech industries. We also find evidence that the impact of innovation activity (proxied by R&D expenditure) on productivity depends on market structure and technological characteristics, with a stronger impact for technological leaders in high-tech industries. In addition, anti-competitive product market regulations are negatively associated with productivity performance. The negative effect is larger the further a country is from the technological frontier, because such regulations hinder the process of technology adoption. Finally, there is also evidence in the ...